CORRELATION BETWEEN MORTALITY PREDICTION AND LENGTH OF STAY IN THE INTENSIVE CARE UNIT - Retno Sumara; Nugroho Ari Wibowo; Andre Arianto; Diah Priyantini (Universitas Airlangga, 2026)
Introduction: Length of stay (LOS) is one of the indicators of the success of care services in the Intensive Care Unit (ICU). Several factors influence how long patients remain in the ICU, including a high mortality prediction score, which may affect the recovery process. The Aim of this study is o analyze the correlation between mortality prediction and LOS among ICU patients. Methods: A correlational analytic study with a retrospective approach was conducted among adult patients aged ≥18 years who had been treated in the ICU, had complete electronic medical record data, and had an APACHE II score recorded during the previous 11 months (March 2023–January 2024). A total of 142 respondents were recruited using purposive sampling. The instrument used in this study was the APACHE II score, and the data were analyzed using Spearman’s rho. Results: LOS of ≥5 days was observed in 63.4% of patients and was distributed across APACHE II score ranges of 15–19 (0.7%), 20–24 (0.7%), 25–29 (2.8%), 30–34 (4.9%), and ≥35 (54.2%). A significant correlation was found between mortality prediction and LOS (p < 0.001). Conclusions: Mortality prediction in ICU patients is correlated with LOS. This indicates that the higher the predicted mortality score, the longer the patient’s length of stay in the ICU